Analisis Survival pada Tungsten dan Degradasi Bearing Menggunakan Regresi Weibull - Gimma Sefira Alamsya; Sutawanir Darwis (UNISBA Press, 2021)
Abstract. Many products are needed by humans in various industries that’s why the selection of materials must be in accordance with the needs because it will affect the quality of the machine. Tungsten carbide is one of the working materials used because of its strong. Bearing is one of the results of the manufacture of tungsten carbide material that acts as a support for a shaft so that it always rotates without friction. Survival analysis will be used to determine the resistance of a machine's strength. The Weibull distribution has a small functional sample size for failure accuracy. We will discuss the application of Weibull regression with the Maximum Likelihood Estimation (MLE) as parameter estimates. This study uses data from the University of Durham, by Braiden, Green and Wright (1982) from experimental results of the stress level test of tungsten carbide cobalt alloy which produces data on stress rates and failure stresses. Tests on 5 different stress rates against twelve observations and it is proven that the stress rate has a significant effect on failure stresses. Then the next data is bearing vibration data from Prognostics and Health Management, FEMTO ST-Institute which consists of 17 bearings with horizontal and vertical directions so that in total there are 34 observations. With time to failure data as the dependent variable and speed and load as independent variables. The result is that only variable speed has a significant effect on time to failure. Abstrak. Banyak produk yang dibutuhkan manusia di berbagai industri itulah mengapa pemilihan bahan harus sesuai dengan kebutuhan karena akan mempengaruhi kualitas mesin. Tungsten karbida merupakan salah satu material kerja yang digunakan karena sifatnya yang kuat. Bearing adalah salah satu hasil pembuatan material tungsten karbida yang berperan sebagai tumpuan sebuah poros agar selalu berputar tanpa adanya gesekan. Akan digunakan analisis survival untuk mengetahui ketahanan kekuatan suatu mesin. Distribusi weibull memiliki bentuk fungsional sampel yang kecil untuk keakuratan kegagalan. Akan dibahas penerapan regresi weibull dengan metode Maximum Likelihood Estimation (MLE) sebagai taksiran parameter. Penelitian ini menggunakan data sekunder University of Durham, oleh Braiden, Green and Wright (1982) hasil eksperimen uji tingkat tekanan paduan tungsten karbida kobalt alloy yang menghasilkan data stress rates dan failure stresses. Pengujian pada 5 stress rates berbeda terhadap dua belas observasi dan terbukti bahwa stress rate berpengaruh secara signifikan terhadap failure stresses. Lalu data selanjutnya adalah data vibrasi bearing dari Prognostics and Health Management, FEMTO ST-Institute yang terdiri dari 17 bearing dengan arah horizontal dan vertikal sehingga ditotalkan ada 34 observasi. Dengan data time to failure sebagai variabel dependen serta speed dan load sebagai variabel independent. Dihasilkan bahwa hanya variabel speed berpengaruh seccara signifikan terhadap time to failure.